2020
DOI: 10.3390/ijms21186751
|View full text |Cite
|
Sign up to set email alerts
|

Distinct TP53 Mutation Types Exhibit Increased Sensitivity to Ferroptosis Independently of Changes in Iron Regulatory Protein Activity

Abstract: The tumor suppressor gene TP53 is the most commonly mutated gene in human cancer. In addition to loss of tumor suppressor functions, mutations in TP53 promote cancer progression by altering cellular iron acquisition and metabolism. A newly identified role for TP53 in the coordination of iron homeostasis and cancer cell survival lies in the ability for TP53 to protect against ferroptosis, a form of iron-mediated cell death. The purpose of this study was to determine the extent to which TP53 mutation status affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Furthermore, we found that the low FPscore subtype showed more TP53 mutations than the high FPscore subtype; additionally, the TP53 pathway was activated in tumors with a high FPscore (Figure 4C; Figure 5G). Therefore, these findings indicate that TP53 may regulate ferroptosis in OSCC cells and are consistent with those of recent studies showing that TP53 and the tumor-associated mutant TP53 may play import roles in ferroptosis of cancer cells [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found that the low FPscore subtype showed more TP53 mutations than the high FPscore subtype; additionally, the TP53 pathway was activated in tumors with a high FPscore (Figure 4C; Figure 5G). Therefore, these findings indicate that TP53 may regulate ferroptosis in OSCC cells and are consistent with those of recent studies showing that TP53 and the tumor-associated mutant TP53 may play import roles in ferroptosis of cancer cells [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to our results, lipid peroxidation in the mutant p53 R273H NCI–H1299 cells did not increase in response to erastin, due to their higher levels of basal lipid peroxidation. Altogether, the mechanisms contributing to increased ferroptotic sensitivity in mutant p53 expressing cells are complex and may not be consistent between distinct TP53 mutation types [ 71 , 75 ]. However, with AF, we were able to kill p53 R273H overexpressing cells in a ferroptotic fashion via GPX4 inactivation and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 is a well-known tumor suppressor gene involved in regulating the cell cycle and negative regulation of cell division by a series of genes [ 23 , 24 ]. Recent studies have found that TP53 can have a role in the process of ferroptosis [ 25 , 26 ]. Numerous studies have taken TP53 as a marker gene of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%